مقاصد الوقف في الشريعة: تأصيلاً وتطبيقاً - الحطاب، عبدالرحمن بن علي مقبل (مؤسسة ساعي لتطوير الأوقاف, 2021)
الوقف مما اختصت به الشريعة الإسلامية عن جميع الشرائع السابقة؛ ولها في شرعه مقاصد مرعية، يحسن وضعها في عين الاعتبار عند النظر في أحكامه، والترجيح بين مسائله المختلف فيها، وقد كشف البحث عن شيء من تلك المقاصد، مع ذكر لأهم القواعد المقاصدية في هذا الباب. وخلاصة ما ورد في البحث تمهيد ومبحثان: وفي التمهيد تعرض البحث إلى: تعريف الوقف، وأدلة مشروعيته، وأنواعه باختصار، ثم كان الحديث عن المقاصد العامة للوقف في مبحثه الأول: وتلك المقاصد باختصار هي: تحقيق العبودية، والدوام والاستمرار على العمل الصالح، وتيسير الأموال ودورانها، والوضوح، والعدل، والحرية، وأخيرا التعاون والتكافل الاجتماعي. وخصص المبحث الثاني لذكر أهم القواعد المقاصدية المؤثرة في أحكام الوقف، وهي: ١. قصد الشارع من المكلف أن يكون قصده موافقا لقصده في التشريع. ٢. القواعد المقاصدية المتعلقة بالمصالح والمفاسد. ٣. أن مقصود الشارع في الأعمال دوام المكلف عليها. ٤. رفع الحرج. وصلى الله على نبينا محمد وعلى آلة وصحبه أجمعين.
All praise is due to Allah alone, and may Allah's Peace and Blessings be upon His Final Messenger, having said that: Waqf is something which distinguishes the Islamic sharia from all the other preceding divine legislations, the Islamic sharia intended regarded objectives in waqf that should be taken into consideration when contemplating its rulings, and when preponderance between the matters in which there is difference of opinion. This research has revealed some of these objectives, in addition to indicating the most important rules pertaining to Islamic objectives in this title. The following is a summary of what was stated in the research that consists of a preface and two sections: The preface briefly tackles the definition of waqf, and the evidences of its legitimacy, and its types. Then, the research touches upon the generic purposes of waqf in the first section, which are in short: The actualization of servitude, the continuation of good deeds, fund management and circulation, clarity, justice, freedom, and finally cooperation and social solidarity. The second topic is devoted to the most important purpose-oriented rules affecting the provisions of the endowment, which are: 1. The legislators purpose from the designated person; that is to say that his purpose shall correspond to his purpose in the legislation. 2. The purpose-oriented rules related to the interests and vices. 3. The legislators purpose in matters is the designated person keeping on them 4. Mitigate difficulties (Raf al-haraj). May Allah send His peace and blessings upon our Prophet Mohammed, his family and all of his companions.
Keywords: الوقف الإسلامي -- الأعمال الخيرية -- أحكام الوقف